2012
DOI: 10.5812/iranjradiol.6686
|View full text |Cite
|
Sign up to set email alerts
|

Value of Proton-MR-Spectroscopy in the Diagnosis of Temporal Lobe Epilepsy; Correlation of Metabolite Alterations With Electroencephalography

Abstract: BackgroundEpilepsy, a well-known mostly idiopathic neurologic disorder, has to be correctly diagnosed and properly treated. Up to now, several diagnostic approaches have been processed to determine the epileptic focus.ObjectivesThe aim of this study was to discover whether proton-MR-spectroscopic imaging (MRSI) aids in the diagnosis of temporal lobe epilepsy in conjunction with classical electroencephalography (EEG) findings.Patients and MethodsTotally, 70 mesial temporal zones consisting of 39 right hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
10
0
5
Order By: Relevance
“…The results of this study showed that the degree of tNAA reduction is probably indicative of neuronal dysfunction [86]. H. Aydin et al also suggested the MRSI sensitivity index for lateralization in the left and right hippocampi, which were 100% and 92% respectively according to EEG findings [98].…”
Section: 2the Relationship Between Eeg Finding and 1 H-mrs Alteratmentioning
confidence: 75%
See 1 more Smart Citation
“…The results of this study showed that the degree of tNAA reduction is probably indicative of neuronal dysfunction [86]. H. Aydin et al also suggested the MRSI sensitivity index for lateralization in the left and right hippocampi, which were 100% and 92% respectively according to EEG findings [98].…”
Section: 2the Relationship Between Eeg Finding and 1 H-mrs Alteratmentioning
confidence: 75%
“…The results regarding correlations between the distribution of metabolic alterations and interracial EEG spikes showed a moderate level of concordance in the lateralization of TLE and ETLE patients [10, 44,52,53,86,97,98]. T. Hammen et al found that tNAA values and the degree of Interictal Epileptiform Discharges (IEDs) in EEG (p=0.04) have a negative correlation.…”
Section: 2the Relationship Between Eeg Finding and 1 H-mrs Alteratmentioning
confidence: 99%
“…Salmenpera et al (26) found that MRS lateralized seizures focus in up to 88% of TLE patients. Aydin et al (27) reported that 1H-MRS offer a lot of qualitative and quantitative data which can help to localize the epileptic lesions and provide an insight into biophysical and biochemical processes related to epileptic seizures. They concluded that the sensitivity of MRS for lateralization epileptic focus was 96%, with specificity was 55%.…”
Section: Discussionmentioning
confidence: 99%
“…Third, H-MRS was evaluated: Multivoxel approach with PRESS voxel excitation by band-selective inversion with gradient dephasing, water-lipid suppression and spatial encoding by chemical shift imaging with high resolution at all three dimensions via 3D-TE: 135 acquisition [4][5][6]9,[20][21][22][23]. With the application of Hamming filter; Effective standard voxel size of 1 × 1 × 1.5 cm was obtained, magnetic field homogeneity was optimized by using both automated and manual shimming, phase encoding was applied to produce 3D-MR spectroscopic arrays of proton spectra throughout the prostate [2,4,5,7,21,24], after post-processing of the time-domain by zero filling to 1024 points, multiplication by Hanning filter, Fourier transformation and phase-baseline correction, spectral data was analyzed to provide standard deviation and peak estimates of choline(Cho), citrate(Cit) and creatine(Cre) resonances, Cit resonance was found at 2.6 ppm, Cre at 3.0 and Cho resonance at 3.2 ppm, respectively [4,6,9,21,23,[25][26][27][28]. For further analysis, Cho/ Cit and Cho + Cre/Cit ratios were used for the tumour depiction; Voxels with more than 30% tumour based on biopsy, were taken as positive ROI for the presence of cancer.…”
Section: Methodsmentioning
confidence: 99%